Selling Its Soul? Private Equity and the Commercialization of the Attest Profession - Donahoo, Nicole; Nielson, Christy S.; Pickerd, Jeffrey (The Accounting Review, 2026)
ABSTRACT The recent influx of deals between accounting and private equity (PE) firms has raised concerns regarding potential implications for the attest profession. We interview 20 attest partners from PE-backed accounting firms, along with four experienced professionals, to examine how these partnerships affect the attest practice. Using Freidson’s (2001) theory of professional autonomy as a theoretical lens, we find that despite independence requirements mandating PE-backed firms separate from their attest function, firms largely retain a one-firm mentality. Moreover, although attest firms retain responsibility for audit execution, PE firms influence attests’ strategic priorities through ROI targets, increased strategic acquisitions, evolved compensation structures, and reevaluated client portfolios. These dynamics underscore a PE-driven shift toward commercialism, potentially eroding—although not eliminating—the attest profession’s professional ideals of public service. This stifling of professionalism raises ethical concerns about PE-driven commercialism amid the growing uncertainty raised by respondents around the future of PE-backed firms. Data Availability: Available upon request. JEL Classifications: M4; M40.